Prevention and Treatment Guideline for Postoperative Nausea and Vomiting by the Royal College of Anesthesiologists of Thailand - Wittayapairoj, Aumjit (Thai Journal of Anesthesiology, 2021)
Postoperative nausea and vomiting (PONV) is one of the most common anesthesia-related complications. It is associated with many undesirable conditions, for example unplanned hospital admission for one-day surgery cases. The Royal College of Anesthesiologists of Thailand (RCAT) established this guideline aimed to reduce the incidence and severity of PONV for adults or pediatrics those at risk for PONV. The guideline was provided the recommendation on identifying high-risk patients, modified the feasible baseline of PONV risks, medications of choices available in our country for prevention and rescue treatment of PONV.